Cultural identity in Roman Celtiberia - Rose, F (2003)
﻿ This thesis presents a study of changing constructions and perceptions of cultural identity over the period 300 BC to AD 100 in the region of northern central Spain known in antiquity as Celtiberia. Its primary focus is iconography, with images of male and female figures of particular interest. The iconography is used to map the continuities and discontinuities in a sense of Celtiberian identity, and considers the effect that interaction with non-Celtiberians, including Celts and Iberians but especially with Romans, had on this identity. A theoretical framework in which to study 'cultural identity' is proposed in the Prolegomena. After the Prolegomena, the thesis is divided into six chapters. Chapter One, Celtiberia in its Historical and Cultural Context, examines the development of Celtiberian culture and Celtiberian settlements over time, and the changes that occurred after the arrival of Romans. Chapter Two, Metallurgy and Metal Objects, looks at three categories of metal objects (fibulae, hospitium tesserae, and armaments) and asks whether the horseman motif, an important iconographic element in this thesis, is emblematic of a 'warrior aristocracy'. Chapter Three, Human and Animal Figures on Painted Pottery, studies the range of human figures found on Celtiberian ceramic vessels, considering the types of scenes and figures that were most popular. Chapter Four, Coins from Pre-Roman and Early Imperial Celtiberia, traces the development of numismatic images in the region. This chapter emphasises the so-called transitional coins, which represent the first time that Celtiberian cities were publicly identified with Roman authority on official media. Chapter Five, Men's Funerary Monuments, returns to critical analysis of the horseman motif, focusing on stelai with relief images of male figures on horseback. Chapter Six, Women's Funerary Monuments, examines the most popular visual language for Celtiberian women, the 'funerary banquet,' and places stelai bearing this theme in their wider social context. A concluding section discusses Celtiberian iconography as a whole. It also considers the role that language - Celtiberian and/or Latin - played alongside the images, and whether the phenomena of bilingualism and Latinisation of names bear 'cultural identity' significance.